Church and State in Old and New Worlds: Church and State In Old and New Worlds - Carey, Hilary M. (Brill's Series in Church History and Religious Culture Ser., 2010)
Drawing on a diverse range of case studies in both the Old World of Europe and the New World of the European settler societies in the United States, Australia and New Zealand this volume offers an original perspective on the conduct of church-state relations and how these have been reshaped by translation from the Old to the New Worlds.